Amphiphilic iron(ii) spin crossover coordination polymers: crystal structures and phase transition properties. Issue 5 (18th December 2018) - Weihermüller, Johannes; Schlamp, Stephan; Milius, Wolfgang; Puchtler, Florian; Breu, Josef; Ramming, Philipp; Hüttner, Sven; Agarwal, Seema; Göbel, Christoph; Hund, Markus; Papastavrou, Georg; Weber, Birgit
Abstract : A cooperative spin transition and thin platelet formation is observed for 1D coordination polymers of amphiphilic iron(ii ) spin crossover complexes. Abstract : Iron(ii ) coordination polymers with an N2 O2 coordinating Schiff base-like equatorial ligand bearing different alkyl chain lengths (C16, C18, C20, and C22) and 1, 2-bis(4-pyridyl)ethyne, 1, 2-bis(4-pyridyl)ethene or 1, 2-bis(4-pyridyl)ethane as bridging ligand are synthesized. All complexes display a rather similar abrupt spin transition above room temperature, which is investigated using magnetic measurements and Mössbauer spectroscopy. Variation of the bridging ligand and the alkyl chain lengths allows fine tuning of the transition temperature in the range between 338 K and 357 K. Single crystal X-ray structure analysis of two coordination polymers and one of the starting complexes reveals the formation of a lipid layer-like arrangement of the amphiphilic complexes in all cases. Further characterization by thermal gravimetric analysis, differential scanning calorimetry, X-ray powder diffraction, and polarized optical microscopy show in all cases solid–solid phase transitions. Those transitions determine the spin crossover behavior and depend on the crystal packing that is controlled by the alkyl chains in the outer periphery of the ligand. Thus, with the presented system the spin crossover properties are controlled by small alterations of the ligand structures. With respect to technological applications, spin coating is shown to be suitable for the processing of the complexes as thin films and furthermore thin platelets of the complexes can be generated by delamination techniques.